Designing of highly active g-C3N4/Co@ZnO ternary nanocomposites for the disinfection of pathogens and degradation of the organic pollutants from wastewater under visible light. Issue 4 (August 2021) - Qamar, Muhammad Azam; Javed, Mohsin; Shahid, Samia; Iqbal, Shahid; Abubshait, Samar A.; Abubshait, Haya A.; Ramay, Shahid M.; Mahmood, Asif; Ghaithan, Hamid M.
Abstract: Photocatalytic degradation of pollutants and disinfection of pathogens under sunlight is a propitious approach to solve the problem of environmental pollution. Herein, we fabricated a series of heterostructure nanocomposites (NCs) by the incorporation of 5% Co@ZnO nanoparticles (NPs) with diverse contents (10–75 wt%) of graphitic carbon nitride (g-C3 N4 ). An inimitable ternary nanocomposite designed by integrating g-C3 N4 and Co@ZnO produced a large number of heterojunctions and active sites for contaminant photocatalysis. The characterization of the fabricated samples was accomplished by XRD, FTIR, SEM, TEM, UV-Vis spectroscopy, BET surface area, and transient photocurrent response. Among the series of (0–9%) Co@ZnO NPs, the 5% Co@ZnO NPs presented maximum methylene blue (MB) photocatalytic degradation under sunlight. Fascinatingly, the ternary heterostructure (60% g-C3 N4 /5% Co@ZnO) developed by the incorporation of 5% Co@ZnO NPs with 60% g-C3 N4 demonstrated an appreciable improvement in photocatalytic activity and completely degraded MB dye in 60 min as compared to 57% by 5% Co@ZnO NPs. The antibacterial efficiency of the photocatalysts was investigated employing the good diffusion procedure counter to Gram-positive (G+ve) and Gram-negative (G-ve) microbes. Ternary 60% g-C3 N4 /5% Co@ZnO heterostructure demonstrated an outstanding antibacterial action compared to its counterparts. The enriched photocatalytic and bactericidal propensity of the 60% g-C3 N4 /5% Co@ZnO NC was principally endorsed to the synergic effects of the heterojunctions created at the g-C3 N4 and Co@ZnO NPs interface. The purposed study gives a good perceptiveness for designing an appropriate visible‐light‐driven photocatalyst with good environmental remediation applications. Graphical Abstract: ga1 Highlights: Highly efficient Co@ZnO NC has been successful integration with fabric like g-C3 N4 sheets. g-C3 N4 /Co@ZnO NC produced a large number of heterojunctions and active sites for catalysis reactions. g-C3 N4 /Co@ZnO NC demonstrated 100% dye degradation in 60 min. g-C3 N4 /Co@ZnO NC exhibited maximum bactericidal action against Staphylococcus aureus (G+ ve).